Comparison of originator and biosimilar therapeutic monoclonal antibodies using comprehensive two-dimensional liquid chromatography coupled with time-of-flight mass spectrometry. Issue 7 (2nd October 2016) - Sorensen, Matthew; Harmes, David C.; Stoll, Dwight R.; Staples, Gregory O.; Fekete, Szabolcs; Guillarme, Davy; Beck, Alain
ABSTRACT: As research, development, and manufacturing of biosimilar protein therapeutics proliferates, there is great interest in the continued development of a portfolio of complementary analytical methods that can be used to efficiently and effectively characterize biosimilar candidate materials relative to the respective reference (i.e., originator) molecule. Liquid phase separation techniques such as liquid chromatography and capillary electrophoresis are powerful tools that can provide both qualitative and quantitative information about similarities and differences between reference and biosimilar materials, especially when coupled with mass spectrometry. However, the inherent complexity of these protein materials challenges even the most modern one-dimensional (1D) separation methods. Two-dimensional (2D) separations present a number of potential advantages over 1D methods, including increased peak capacity, 2D peak patterns that can facilitate unknown identification, and improvement in the compatibility of some separation methods with mass spectrometry. In this study, we demonstrate the use of comprehensive 2D-LC separations involving cation-exchange (CEX) and reversed-phase (RP) separations in the first and second dimensions to compare 3 reference/biosimilar pairs of monoclonal antibodies (cetuximab, trastuzumab and infliximab) that cover a range of similarity/disimilarity in a middle-up approach. The second dimension RP separations are coupled to time-of-flight mass spectrometry, which enables direct identification of features in the chromatograms obtained from mAbs digested with the IdeS enzyme, or digestion with IdeS followed by reduction with dithiothreitol. As many as 23 chemically unique mAb fragments were detected in a single sample. Our results demonstrate that these rich datasets enable facile assesment of the degree of similarity between reference and biosimilar materials.